Vector Control of Three-Phase Induction Motor with Two Stator Phases Open-Circuit - Seyed Hesam Asgari; Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris (Institute of Advanced Engineering and Science, 2015)
Variable frequency drives are used to provide reliable dynamic systems and significant reduction in usage of energy and costs of the induction motors. Modeling and control of faulty or an unbalanced three-phase induction motor is obviously different from healthy three-phase induction motor. Using conventional vector control techniques such as Field-Oriented Control (FOC) for faulty three-phase induction motor, results in a significant torque and speed oscillation. This research presented a novel method for vector control of three-phase induction motor under fault condition (two-phase open circuit fault). The proposed method for vector control of faulty machine is based on rotor FOC method. A comparison between conventional and modified controller shows that the modified controller has been significantly reduced the torque and speed oscillations.